Basileia
1 online resource (266 pages)
Keywords: Basileia brings together 18 essays on the topic of Imperium and Culture in the Byzantine Empire, from the fourth to the fifteenth centuries. The volume is dedicated to Elizabeth and Michael Jeffreys, who number among the founding members of the Australian Association for Byzantine Studies and whose contribution to the field is internationally recognised. Each of the honorands has contributed a chapter; other contributors include Roger Scott, Pauline Allen, Brian Croke, Ann Mullett, Geoffrey Nathan, Lynda Garland, Bronwen Neil, Andrew Gillett, Amelia Brown, Andrew Stone, Nigel Westbrook and Erika Gielen. This collection will have a broad appeal to those interested in the complex relationship between imperial rule and culture in Byzantium. The volume includes 50 colour and black-and-white images.